Prevalence and impact of a chronic total occlusion in a non-infarct-related artery on long-term mortality in diabetic patients with ST elevation myocardial infarction. Issue 24 (7th October 2010) - Claessen, Bimmer E P M; Hoebers, Loes P; van der Schaaf, René J; Kikkert, Wouter J; Engstrom, Annemarie E; Vis, Marije M; Baan, Jan; Koch, Karel T; Meuwissen, Martijn; van Royen, Niels; de Winter, Robbert J; Tijssen, Jan G P; et al.
Abstract : Background: Recently, a chronic total occlusion (CTO) in a non-infarct-related artery (non-IRA) and not multivessel disease (MVD) alone was identified as an independent predictor of mortality after ST elevation myocardial infarction (STEMI). Patients with diabetes mellitus (DM) constitute a patient group with a high prevalence of MVD and high mortality after STEMI. The prevalence of CTO in a non-IRA was studied and its impact on long-term mortality in STEMI patients with DM was investigated. Methods: Between 1997 and 2007 4506 patients with STEMI were admitted and treated with primary percutaneous coronary intervention (PCI). Patients with DM were identified. The patients were categorised as having single vessel disease (SVD), MVD without CTO and CTO based on the angiogram before PCI. Results: A total of 539 patients (12%) had DM. MVD with or without a CTO was present in 33% of non-diabetic patients and in 51% of diabetic patients. The prevalence of a CTO in a non-IRA was 21% in STEMI patients with DM and 12% in STEMI patients without DM (p<0.01). Kaplan–Meier estimates for 5-year mortality in STEMI patients with DM were 25%, 21% and 47% in patients with SVD, MVD without a CTO and MVD with a CTO in a non-IRA, respectively. A CTO in a non-IRA was an independent predictor of 5-year mortality (HR 2.2, 95% CI 1.3 to 3.5, p<0.01). Conclusion: The prevalence of a CTO in a non-IRA was increased in STEMI patients with DM. The presence of a CTO in a non-IRA was a strong and independent predictor of 5-year mortality. These results suggest that, particularly in the high-risk subgroup of STEMI patients with DM, MVD has prognostic implications only if a concurrent CTO is present.